Early years autism and bilingualism: An interpretative phenomenological analysis of parent perceptions during lockdown. (November 2022) - Oudet, Sarah; Howard, Katie; Durrleman, Stephanie
Aim: This study explores how bilingual parents of autistic children made language decisions for their families, how the event of the SARS-CoV-2 pandemic and subsequent lockdown impacted the communication environment of their households, and whether these experiences affected their language habits. Method: Semi-structured interviews were conducted with five bilingual parents of autistic children who lived through lockdown in France. Data were analysed using interpretative phenomenological analysis. Demographic and background information was collected using an adapted version of the Questionnaire for Parents of Bilingual Children. Results: Participants reported conflicting advice given by a range of practitioners. Parents expressed differing beliefs about the impact of language choices on their children. Parents described active engagement with their children's home-learning as generally positive. Parents identified an increase in children's exposure to their first language during the lockdown. Parents reported an increase in children's overall communication abilities. Conclusion: Parents believed that their children's positive communication development during lockdown was related to increased exposure to their first language(s), and direct involvement in their children's learning programs.